Implementation of Physical Education Learning in Pascal Secondary School, Hanoi, Vietnam - Tarigan, Elsa Silviana (Universitas Negeri Semarang, 2018)
The purpose of this study was to know the description result of Physical Education learning at Pascal Secondary School, Hanoi, Vietnam 2016. The method research is used descriptive qualitative. The time of research implementation is in September 2016. The techniques of data collection are observation, interview, and documentation. Analyzing data through data reduction, present data, and summarize results. The results showed the activity consisting of learning plan of Physical Education covering syllabus, preparing instructional media, and learning tools / equipment. Implementation of learning is with allocation of 45 minutes per meeting which consists of preliminary activities, core activities, and closing activities. The physical education learning assessment consists of 3 domains of attitude through observation methods, knowledge through written tests, and skills through practice methods. The learning materials Physical Education in Pascal Secondary School, Hanoi, Vietnam consists of soccer games, badminton, volley ball, rhythmic gymnastics and cauda. The conclusion of this study is the average implementation of physical education learning in Pascal Secondary School, Hanoi, Vietnam, have optimaly.